Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

How do you find the sum of the roots of the roots of:\[{x^2} - 5m + 12\]?

seo-qna
Last updated date: 16th Jul 2024
Total views: 378k
Views today: 7.78k
Answer
VerifiedVerified
378k+ views
Hint: Here in this question you have to learn the well known equation given by siddhicharan known as sridharacharya equation which helps in finding the roots of quadratic equation and nature of roots of quadratic equation. The rule says for any quadratic equation \[a{x^2} + bx + c\] the determinant of equation is \[\sqrt {{b^2} - 4ac} \] and roots can be obtained from \[\dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\], and nature of roots can be seen as real root or complex root.

Formulae Used: Sridharacharya rule which says for any quadratic equation \[a{x^2} + bx + c\] the determinant of equation is \[\sqrt {{b^2} - 4ac} \] and roots can be obtained from \[\dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\], and nature of roots can be seen as real root or complex root.
And \[\sqrt { - 1} = i\]

Complete step by step solution:
 Given equation: \[{x^2} - 5m + 12\]
Comparing this equation with general quadratic equation \[a{x^2} + bx + c\]
We get,
Value of \[a = 1,b = - 5,c = 12\]
Now, determinant D equals
\[
  D = \sqrt {{b^2} - 4ac} \\
   = \sqrt {{{( - 5)}^2} - 4(1)(12)} \\
   = \sqrt {25 - 48} \\
   = \sqrt {( - 23)} \\
   = \sqrt { - 1} \times \sqrt {23} \\
   = 23i\,(\sin ce\,\sqrt { - 1} = i) \\
 \]
Here we are getting the negative value of discriminant hence we will get complex roots.
Now, for roots of equation we use
\[\dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
We get,
 \[
   = \dfrac{{ - ( - 5) + 23i}}{{2(1)}},\,\dfrac{{ - ( - 5) - 23i}}{{2(1)}} \\
   = \dfrac{{5 + 23i}}{2},\,\dfrac{{5 - 23i}}{2} \\
 \]
Hence roots of equation are \[\dfrac{{5 + 23i}}{2},\,\dfrac{{5 - 23i}}{2}\] and sum of roots are:
\[
   \Rightarrow \dfrac{{5 + 23i}}{2} + \dfrac{{5 - 23i}}{2} \\
   \Rightarrow \dfrac{{5 + 23i + 5 - 23i}}{2} = \dfrac{{10}}{2} = 5 \\
 \]

Note: Here in this question mid term splitting is not used for finding the roots because it is very difficult to think of the split terms for the middle term of the equation, which follows the condition of the mid term split rule for factorization. But if you think you can find such terms then definitely you can use a mid term splitting method also.